Welding simulation of corrugated web girders - Part 1: Effect of manufacturing on residual stresses and imperfections. (January 2020) - Kollár, D.; Kövesdi, B.
Abstract: Steel I-girders with corrugated webs have been widely used in the past decades, especially in bridges. Although, there are several specialities in their structural behaviour which needs further investigation. Buckling resistance of slender structures is sensitive to imperfections due to residual stresses and initial geometric imperfections. Shear buckling resistance of conventional I-girders with flat webs have been extensively analysed previously. However, the sensitivity of corrugated web girders to imperfections need further investigations. The current paper introduces the finite element model of corrugated web girders developed for modelling thermal cutting and welding. The developed numerical model is capable of simulating thermal phenomena during manufacturing, and it is a useful tool to determine residual stresses and initial geometric imperfections depending on welding variables. Manufacturing imperfections are calculated for several girders with different corrugation profiles. The obtained tendencies are evaluated and discussed in the current paper (Part I). In the accompanying paper [1] (Part 2) the effect of manufacturing imperfections are analysed on the shear buckling resistance of corrugated web girders. The whole numerical simulation process from manufacturing simulation to resistance determination is presented, and their advantages in the design are demonstrated. Highlights: Residual stresses and imperfections of corrugated web girders are analysed. Laboratory tests on welding-induced strains are executed during welding. Numerical model has been developed to simulate the welding procedure. Numerical model is validated by comparison of test and simulation results. Typical residual stress patterns are determined and evaluated.